A contemporary view of work design: how do job complexity and job autonomy shape proactive work behavior through role breadth self-efficacy? - Beynaz Uysal; Cavide Uyargil (Trakya Üniversitesi İktisadi ve İdari Bilimler Fakültesi E-Dergi, 2025)
This study investigates how work design influences proactive work behavior (PWB) by considering specific key work characteristics and a motivational mediating variable. This study identifies the roles of job complexity and autonomy, as well as the mediating role of role breadth self-efficacy (RBSE), in shaping proactive work behavior (PWB). This research employed a quantitative approach to gather and analyze data. Responses were collected from 350 employees using a structured questionnaire and a convenience sampling technique. SPSS served as the primary tool for data analyze, including Pearson correlation and regression analysis, and the mediation effect was assessed using the Process Macro in combination with the bootstrap technique. According to the results, PWB is positively affected not only by job complexity but also by job autonomy and RBSE acts as an important mediator in these relationships. The findings provide important theoretical and practical perspectives for organizations seeking to build a proactive workforce capable of coping with dynamic work environments through effective work design.